PEMBUKUAN SEDERHANA PADA KELOMPOK KULINER PONDOKAN KELANA - Sandra, Evita; Furbani, Adelya Dwi; Prayoga, Angga; Syah, Ardian; Rahmawati, Debby Ayu; Elfadira, Meidina; Fadillah, Muhammad Rahmat; Dewi, Novika Lias; Bella, Nur Zhaza; Alifta, Siti Nur; Kamal, Tiara Syafira (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
This service aims to provide knowledge about simple bookkeeping for members of the Pondokan Kelana Culinary Group in Penaga Village, Bintan Regency. The method used is a mentoring method in the form of training. In the process of making this simple bookkeeping, there is a recording of financial reports to help mothers make it easier to manage business finances. The analysis carried out focuses on the problems of Business Bookkeeping. This analysis resulted in solving the problem in the form of a program that we carried out, namely "Assistance in Making Simple Bookkeeping for the Pondokan Kelana Culinary Group" in Penaga Village and conducting training on simple bookkeeping for UMKM.